If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying R + -24 = -14 Reorder the terms: -24 + R = -14 Solving -24 + R = -14 Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + R = -14 + 24 Combine like terms: -24 + 24 = 0 0 + R = -14 + 24 R = -14 + 24 Combine like terms: -14 + 24 = 10 R = 10 Simplifying R = 10
| t(3t-2)=0 | | (-75)=25 | | 4x(2)=16 | | 2x-4=9x-35 | | (75)=25 | | 5x+5=115+x | | 2x^2+18x+36= | | 71-7x=29x+19x | | 4-c=16 | | 3x^2-16x-35= | | 168=3x-12 | | -100-8x=9x+19x | | 6x^2-x-7= | | X^2+2x-48=4x-24 | | 168=12-3x | | 6(1-m)=10-2m | | 9x-7+11x-27=180 | | 143-5x=3x+23 | | 62=2(3+6x)+2(x) | | 12(5h-2)=5h+8 | | 3k-13=2(3k-5) | | -x+4(x-1)=12+x | | 3x-9x-7=-6x+2-7 | | 3x-5=2x+x-7 | | 50=2(4+6x)+2(x) | | -8(n-1)=13-7n | | 3x(2)=12 | | 8(-2-4)+12=-52 | | -4(1-6a)=6a-40 | | -16t^2+128t+1344=0 | | 44=2(4+5x)+2(x) | | -4(x+3)(x+3)=-16 |